Age Differences in the Use of Implantable Cardioverter‐Defibrillators Among Older Patients Hospitalized with Heart Failure. (25th February 2013) - HESS, PAUL L.; GRAU‐SEPULVEDA, MARIA V.; HERNANDEZ, ADRIAN F.; PETERSON, ERIC D.; BHATT, DEEPAK L.; SCHWAMM, LEE H.; YANCY, CLYDE W.; FONAROW, GREGG C.; AL‐KHATIB, SANA M.; ,
Age and ICD Use Among Older HF Patients Introduction Practice guidelines recommend the use of ICDs in patients with heart failure (HF) and a left ventricular ejection fraction (LVEF) of ≤ 35% in the absence of contraindications. Methods and Results We performed an analysis of ICD use among patients admitted with HF with LVEF of ≤ 35% and discharged alive from 251 hospitals participating in the American Heart Association's Get With The Guidelines‐HF Program between January 2005 and September 2011. Among 35, 772 guideline‐eligible patients, 17, 639 received an ICD prior to hospitalization (10, 886), during hospitalization (4, 876), or were discharged with plans to undergo ICD placement after hospitalization (1, 877). After adjustment, increasing age was associated with lower ICD use (odds ratio [OR] 0.89, 95% confidence interval [CI] 0.87–0.91 per 5‐year increase in age, P < 0.0001). Compared with patient age < 55 years, older age groups ≥ 65 years were less likely to receive an ICD (P < 0.003). Compared with men in the same age group, women were significantly less likely to receive an ICD; this difference was more marked with increasing age (P value for interaction = 0.006). There was a temporal increase in ICD use (adjusted OR 1.23, 95% CI 1.15–1.31 of ICD use per year) that was similar in each age group (P value for interaction = 0.665). Conclusions Eligible older HF patients age ≥ 65 years were significantly less likely to receive an ICD. With increasing age, women were less likely to receive an ICD than men. ICD use significantly increased over time in all age groups; however, age‐related differences in ICD use persisted.